SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN METODE PROFILE MATCHING DALAM PEMBERIAN REWARD (Studi Kasus: Toserba Fajar Luragung) - Erik Kurniadi; Samsu Ahdiana; Dadan Nugraha (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
Fajar Luragung department store is one of the companies that implements a reward program for employees who deserve it. The reward is an award as a form of corporate gratitude to employees who have worked well. The selection of best employees is the process of evaluation about how well the performance of employees is in accordance with the standards set by the company. However, the number of criterias that must be considered make the selection team confused in determining the best employee to be rewarded. Therefore, a decision support system is needed that can determine the best employees based on many criterias, one of them is the Profile Matching Method. This study uses the Waterfall model system development method and the programming languages used are PHP and MySQL. The final result of this study found that the decision support system with the Profile Matching method was able to overcome the problems in the process of selecting the best employees at the Fajar Luragung Department Store.